The Relationship between Nutrition and Life Satisfaction of Football Players in COVID-19 Period - Balyan, Melih; Zekioglu, Aylin; Basoglu, Umut Davut; Isik, Turan; Tascioglu, Ramazan (Progress in Nutrition, 2021)
Study Objectives: Nutrition and life satisfaction are very important for every living thing, but it has a different importance for individuals who do sports. The aim of this study was to compare the relationship between nutrition and life satisfaction of football players in the COVID-19 period and to evaluate with various variables. Methods: The research was conducted with 306 male players who actively played football in various clubs in the city center of Izmir between 2020 and 2021. The data were collected by using a personal information form, a three-factor nutrition questionnaire, and a life satisfaction scale. Results: The total scores of the life satisfaction scale differ significantly according to the age groups, income levels, future expectations, and loneliness levels of the football players (p<0.05). The total scores of the life satisfaction scale differ significantly according to their body mass index (BMI) groups, licensed football seniority, and their future expectations (p>0.05). The “4-Factor Nutrition Questionnaire” and subscale total scores of the football players do not differ significantly in terms of loneliness level, age, licensed football seniority, level of income, and level of loneliness (p > 0.05). There is no relationship between the life satisfaction scale of individuals and the subscales of the Nutrition scale (p>0.05). There is a statistically significant positive correlation between the total scores of the “Life Satisfaction Scale” and the “4 Factor Nutrition Questionnaire” (p<0.05). Conclusion: The more people enjoy life and the happier they are in life, the higher their life satisfaction will be. The diet of individuals with high life satisfaction is regular and they eat regularly. Individuals who are healthy and do not have psychological problems have high life satisfaction and healthy nutrition.